Unveiling the relationship between sustainable development and Industry 4.0: A text mining literature analysis - Strazzullo, S. (2023)
This article aims to assess the evolution of the literature on the link between Industry 4.0 and sustainable development. Through a systematic analysis of the literature, a sample of 234 documents was identified, published between 2011 and 2021. Given the large number of papers collected, the text mining approach was performed to analyze the sample of documents. In particular, the latent Dirichlet allocation model was adopted to group articles in different relevant topics starting from two dictionaries belonging to terms both in the domain of Industry 4.0 and in sustainability. As a result, 11 different topics have been identified that link these two domains. The results showed a strong predominance of Industry 4.0 compared to sustainability models that are very focused only on the environmental aspect. In conclusion, this study emphasizes future research potential by highlighting these existing research areas.